In vivo characterization of two additional Leishmania donovani strains using the murine and hamster model. (May 2016) - Kauffmann, F.; Dumetz, F.; Hendrickx, S.; Muraille, E.; Dujardin, J.‐C.; Maes, L.; Magez, S.; De Trez, C.
Summary: Leishmania donovani is a protozoan parasite causing the neglected tropical disease visceral leishmaniasis. One difficulty to study the immunopathology upon L. donovani infection is the limited adaptability of the strains to experimental mammalian hosts. Our knowledge about L. donovani infections relies on a restricted number of East African strains (LV9, 1S). Isolated from patients in the 1960s, these strains were described extensively in mice and Syrian hamsters and have consequently become 'reference' laboratory strains. L. donovani strains from the Indian continent display distinct clinical features compared to East African strains. Some reports describing the in vivo immunopathology of strains from the Indian continent exist. This study comprises a comprehensive immunopathological characterization upon infection with two additional strains, the Ethiopian L. donovani L82 strain and the Nepalese L. donovani BPK282 strain in both Syrian hamsters and C57BL/6 mice. Parameters that include parasitaemia levels, weight loss, hepatosplenomegaly and alterations in cellular composition of the spleen and liver, showed that the L82 strain generated an overall more virulent infection compared to the BPK282 strain. Altogether, both L. donovani strains are suitable and interesting for subsequent in vivo investigation of visceral leishmaniasis in the Syrian hamster and the C57BL/6 mouse model.